2020
DOI: 10.1155/2020/8856135
|View full text |Cite
|
Sign up to set email alerts
|

Comparation of Anti‐Inflammatory and Antioxidantactivities of Curcumin, Tetrahydrocurcuminand Octahydrocurcuminin LPS‐Stimulated RAW264.7 Macrophages

Abstract: Curcumin (CUR) possesses pronounced anti-inflammatory and antioxidant activities. Generally, the clinical application of CUR is restricted due to its apparent unstability and poor absorption, and the biological activities of CUR may be closely associated with its metabolites. Tetrahydrocurcumin (THC) and octahydrocurcumin (OHC) are two major hydrogenated metabolites of CUR with appreciable biological potentials. Here, we comparatively explored the anti-inflammatory and antioxidant activities of CUR, THC, and O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…This study proved the protective effect of curcumin and selenium, alone and in combination with each other, this finding in agreement with previous studies where curcumin showed multiple pharmacological activities, including anti‐inflammation and antioxidant (Xie et al, 2020), and have an essential role in inhibiting the progression of HCC through various pathways (Tan & Norhaizan, 2019; Zhang et al., 2018). Previous studies have shown a potential inverse relationship between selenium levels and the occurrence of HCC (Cheng et al., 2019).…”
Section: Discussionsupporting
confidence: 92%
“…This study proved the protective effect of curcumin and selenium, alone and in combination with each other, this finding in agreement with previous studies where curcumin showed multiple pharmacological activities, including anti‐inflammation and antioxidant (Xie et al, 2020), and have an essential role in inhibiting the progression of HCC through various pathways (Tan & Norhaizan, 2019; Zhang et al., 2018). Previous studies have shown a potential inverse relationship between selenium levels and the occurrence of HCC (Cheng et al., 2019).…”
Section: Discussionsupporting
confidence: 92%
“…A large number of studies have shown that dietary curcumin reduced the mRNA expression and secretion of IL-1β, IL-6, TNFα, and MCP-1 in LPS stimulated RAW 264.7 cells and cisplatin-treated mice. 29,30 Our previous studies verified that the orally-administered DHA enriched phospholipids and triglycerides could decrease the level of inflammatory cytokines, including IL-1β and TNF-α in mice with dextran sodium sulfate-induced colitis. 31 The above results indicated that the intervention of DHA or Cur could inhibit the inflammatory response in the kidney of AKI mice, and it is worth mentioning that DHA-acylated curcumin esters exhibited good anti-inflammatory activities compared with the recombination of Cur and DHA or Cur and DHA alone.…”
Section: Discussionmentioning
confidence: 73%
“…The major metabolite of curcumin, THC, is reported to exhibit stable activity and absorption efficiency and to possess a more favourable bioavailability than that of curcumin [10,26,27]. Xie et al have demonstrated that THC exerts more notable anti-inflammatory and antioxidant activities in LPS-stimulated RAW264.7 macrophages than curcumin does [14]. Moreover, compared with curcumin, THC more effectively suppresses pathways for COX-2 and transforming growth factor β, activated kinase-1, and NF-κB in vivo [13].…”
Section: Discussionmentioning
confidence: 99%
“…Neurodegenerative disorders are commonly associated with oxidative stress-induced inflammation [28,29]. Under LPS stimulation, the TLR4-mediated NF-κB and mitogenactivated protein kinases are activated and iNOS-mediated proinflammatory NO is produced in activated macrophages [14]. LPS is also known to induce COX-2 production in vitro and in vivo [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation